Unidade e fragmentação: em torno da sociologia jurídica de Gunther Teubner - Kroschinsky, Matthaeus (2023)
The aim of this work is a panoramic and contextual presentation of the work of the German professor Gunther Teubner. In Chapter 1 we analyze some main aspects of Max Weber's sociology that allow us to culminate in his concepts of formal and material law, the basis for understanding the phenomenon of juridification for which Teubner's reflexive law sought to present itself as an alternative in the context of law substantive law of the social state. In Chapter 2 we analyze Niklas Luhmann's theory of autopoietic systems, with whom Teubner maintains a fruitful theoretical dialogue to this day. From the third chapter onwards, we effectively begin the analysis of Teubner's thought. To do so, we start with a tripartition of his work into three phases in which a gradual increase in the critical-normative potential is observed. Firstly, we will analyze its reflexive law as an alternative to regulatory law, which already in the 1980s saw its fraying. In Chapter 4 we will analyze legal pluralism. Teubner reads Eugen Ehrlich's living law through luhmannian lens, which allows him to understand how law is linked to the praxis of each social subsystem, producing sui generis legal orders. Finally, we analyze Teubner's civil constitutionalism. In this phase of his work, the German professor intends to expand Luhmann's idea of the Constitution as a structural coupling between law and politics to the coupling between law and other social systems as a way of bringing the guarantees of the rule of law to such legal systems